2023
DOI: 10.1001/jamanetworkopen.2023.27326
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Treatment Initiation Among US Medicaid Enrollees

Abstract: ImportanceDirect-acting antiviral (DAA) treatment for hepatitis C virus (HCV) infection is highly effective but remains underused. Understanding disparities in the delivery of DAAs is important for HCV elimination planning and designing interventions to promote equitable treatment.ObjectiveTo examine variations in the receipt of DAA in the 6 months following a new HCV diagnosis.Design, Setting, and ParticipantsThis retrospective cohort study used national Medicaid claims from 2017 to 2019 from 50 states, Washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Despite availability of highly effective direct‐acting antiviral (DAA) therapies since 2015, studies have found that relatively few patients receive treatment (estimates ranged from 5% to 30%). 7 , 8 , 9 , 10 , 11 Studies in single organizations found that the rate of linkage to specialist care varied by site of testing (65%–78% in outpatient settings received linkage to care vs. 30%–57% in inpatient settings). 2 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Despite availability of highly effective direct‐acting antiviral (DAA) therapies since 2015, studies have found that relatively few patients receive treatment (estimates ranged from 5% to 30%). 7 , 8 , 9 , 10 , 11 Studies in single organizations found that the rate of linkage to specialist care varied by site of testing (65%–78% in outpatient settings received linkage to care vs. 30%–57% in inpatient settings). 2 , 4 …”
Section: Introductionmentioning
confidence: 99%